Keefektifan Pembelajaran Menulis Cerita Fantasi dengan Model Sinektik Berdasarkan Kecerdasan Linguistik (Lingua, 2019)
AbstractThe aim of this research is analyzes the effectiveness of learning to write fantasy stories using the synectic model based on the linguistic intelligence of class VII junior high school students. Fantasy story material in the 2013 curriculum at grade VII junior high school requires teachers to be more creative. Creativity teachers learn by using models in learning. From the results of this research it can be proven that there is effectiveness in learning to write fantasy stories using the synectic model based on linguistic intelligence. The method used in this research is a quasi experiment with data collection techniques using instruments: tests of writing fantasy stories, linguistic intelligence tests, observation of attitude, photos, and interviews. Data normality test using the Kolmogorov Smirnov test. Data homogeneity test using Levense test. Hypothesis testing uses an independent test (t-test). All of these test use the SPSS 20th program. The conclusions of the results of this research is that the application of the synectic model is effectively used in learning to write fantasy story texts based on the linguistic intelligence in class VII junior high school students. Learning to write fantasy stories using the synectic model is more effectively applied to students with high average linguistic intelligence than students with average linguistic intelligence.